2017
DOI: 10.1242/jcs.205922
|View full text |Cite
|
Sign up to set email alerts
|

CDC42 is required for epicardial and pro-epicardial development by mediating FGF receptor trafficking to the plasma membrane

Abstract: The epicardium contributes to multiple cardiac lineages and is essential for cardiac development and regeneration. However, the mechanism of epicardium formation is unclear. This study aimed to establish the cellular and molecular mechanisms underlying the dissociation of pro-epicardial cells (PECs) from the pro-epicardium (PE) and their subsequent translocation to the heart to form the epicardium. We used lineage tracing, conditional deletion, mosaic analysis and ligand stimulation in mice to determine that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Failure to form the epicardial layer was due to a diminished source of epicardial progenitor cells within the PEO, as a result of their decreased proliferative capacity in the absence of SRSF3. However, recombination in the Tg(Gata5-Cre) model also targeted a subset of cardiomyocytes, thus, combined depletion of SRSF3, in most epicardial progenitor cells and a subset of cardiomyocytes, contributed to the severe phenotype, as embryos with impaired epicardial formation generally die at later stages (von Gise et al 2011; Li et al 2017). Early stage embryonic lethality was previously reported in cardiac-specific SRSF3 knockout mice due to impaired cardiomyocyte proliferation and survival (Ortiz-Sánchez et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to form the epicardial layer was due to a diminished source of epicardial progenitor cells within the PEO, as a result of their decreased proliferative capacity in the absence of SRSF3. However, recombination in the Tg(Gata5-Cre) model also targeted a subset of cardiomyocytes, thus, combined depletion of SRSF3, in most epicardial progenitor cells and a subset of cardiomyocytes, contributed to the severe phenotype, as embryos with impaired epicardial formation generally die at later stages (von Gise et al 2011; Li et al 2017). Early stage embryonic lethality was previously reported in cardiac-specific SRSF3 knockout mice due to impaired cardiomyocyte proliferation and survival (Ortiz-Sánchez et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, it was first reported that PE cell clusters detach from the proepicardial surface to form cysts, which then float freely across the pericardial cavity to attach to the myocardium around embryonic day 9 (E9.0) (Komiyama et al 1987). Newer studies in mice suggest that both direct contact between the PE and myocardium and adhesion of free-floating PE cell cysts to the myocardium, underlie this translocation process (Rodgers et al 2008;Li et al 2017). Mice bearing a mutation of Par3, a polarity gene, display disrupted basoapical polarity and impaired cyst formation, suggesting that cell polarity is critical for PE cyst formation (Hirose et al 2006).…”
Section: )mentioning
confidence: 99%
“…Mice bearing a mutation of Par3, a polarity gene, display disrupted basoapical polarity and impaired cyst formation, suggesting that cell polarity is critical for PE cyst formation (Hirose et al 2006). Similarly, an epicardium-specific deletion of Cdc42 also disrupts cell polarity and blocks the formation of PE protrusions and floating epicardial clusters (Li et al 2017). Recent live imaging of PE development and translocation in zebrafish have also found that PE cell release and adhesion occur through both direct contact with the myocardium and with the floating clusters, which are driven by the heartbeat-induced flow of pericardial fluid (Peralta et al 2013;Plavicki et al 2014).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation